Anatomical and Clinical Utility of Salivary Biomarkers for Early Detection and Monitoring of Diabetes and Cardiovascular Disease - Aisha Hassan Brohi, Amna Mughal, Sohaib Farooq, Hira Shafique, Abdur Rauf Hammad, Nadia Mansoor (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetes mellitus (DM) and cardiovascular disease (CVD) are among the leading causes of morbidity and mortality worldwide. Early detection and continuous monitoring are essential to reduce long-term complications. Saliva has emerged as a non-invasive biofluid that reflects systemic alterations, offering potential as a diagnostic tool. Objective: This study aimed to evaluate the anatomical and clinical utility of salivary biomarkers in the early detection and monitoring of diabetes mellitus and cardiovascular disease. Methods: A cross-sectional study was conducted at Dow University Hospital (DUH), Karachi, Pakistan, from June 2022 to June 2023. A total of 100 participants were enrolled, including 40 patients with type 2 diabetes mellitus, 40 patients with cardiovascular disease, and 20 healthy controls. Unstimulated saliva samples were collected and analyzed for glucose, amylase, inflammatory cytokines (IL-6, TNF-α, CRP), oxidative stress markers (MDA, 8-OHdG), and cardiac-specific proteins (troponin I, BNP). Data were analyzed using ANOVA, Chi-square tests, and Pearson correlation. Results: Salivary glucose was significantly elevated in diabetics compared to cardiovascular patients and controls (p < 0.001). Amylase activity was reduced in diabetes, while inflammatory cytokines and oxidative stress markers were raised in both disease groups (p < 0.001). Cardiovascular patients exhibited markedly higher salivary troponin I and BNP compared to other groups (p < 0.001). Correlation analysis showed strong associations between salivary and serum biomarkers, including glucose with fasting blood glucose (r = 0.76, p < 0.001), HbA1c (r = 0.71, p < 0.001), and troponin I with serum troponin (r = 0.82, p < 0.001). Conclusion: Saliva demonstrates strong potential as a non-invasive diagnostic medium for diabetes and cardiovascular disease. Elevated salivary glucose, inflammatory mediators, oxidative stress markers, and cardiac proteins closely reflect systemic disease states. With further validation, salivary diagnostics could complement conventional blood-based investigations and facilitate early detection and longitudinal monitoring in both clinical and community settings. Keywords: saliva, biomarkers, diabetes mellitus, cardiovascular disease, non-invasive diagnostics, oxidative stress, inflammation